CHSY3 can be a Poor Prognostic Biomarker and Mediates Immune Evasion in Stomach Adenocarcinoma - Li, Xinwei; Fan, Yongfei; Zhang, Yue; Wang, Yanyan; Zhao, Menglin; Tang, Mingyue; Li, Huiyuan; Mi, Jiaqi; Geng, Zhijun; Wang, Zishu; Su, Fang (Frontiers in Genetics, 2022)
Background: Chondroitin sulphate synthase 3 (CHSY3) is an important enzyme that regulates glycosylation, but it has not been reported in tumours. This study explored for the first time the oncological features of CHSY3 in stomach adenocarcinoma (STAD). Methods: We analysed CHSY3 expression in STAD through the Cancer Genome Atlas (TCGA) database and verified our findings by immunohistochemical staining and Western blot experiments. The prognostic value of CHSY3 in STAD was analysed through the biological aspects of CHSY3 in STAD, such as communal clinical follow-up survival data, methylation sites, tumour immune microenvironment (TIME) and immune cell surface checkpoints. Finally, the immune-evasion potential of CHSY3 in STAD was assessed on the Tumor Immune Dysfunction and Exclusion (TIDE) website and immunohistochemical staining experiment. Results: CHSY3 overexpression in STAD was associated with a poor prognosis based on immunohistochemical staining and Western blot experiments. Multivariate Cox analysis suggested that CHSY3 could be an independent prognostic risk factor. Pathway enrichment and TIME analysis demonstrated that CHSY3 up-regulated mesenchymal activation and immune activation signals in STAD, while TIDE assessment revealed that the risk of immune evasion was significantly higher in the high CHSY3 expression group than in the low CHSY3 expression group. Risk model scores based on CHSY3-associated immune cell surface checkpoints also presented poor prognosis, and immune evasion was significantly higher in the high-risk group than in the low-risk group. Conclusions: This study analysed CHSY3 from multiple biological perspectives and revealed that CHSY3 can be a biomarker of poor prognosis and mediates the TIME immune-evasion status in STAD.